2016
DOI: 10.1016/j.vaccine.2015.12.042
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal carriage of Streptococcus pneumoniae among children in an urban setting in Brazil prior to PCV10 introduction

Abstract: Information on pneumococcal carriage in the pre-vaccine period is essential to predict and assess the impact of PCV in settings where disease surveillance is particularly difficult. Therefore, we present data on pneumococcal carriage before the introduction of the 10-valent-pneumococcal conjugate vaccine (PCV10) in Brazil. We conducted a prospective study on a cohort of 203 children aged < 5 years-old, randomly selected in an urban community located in the periphery of the city of Salvador, Brazil and followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 38 publications
4
14
1
Order By: Relevance
“…The nasopharyngeal carriage rate of 25.3% in the current study is higher than a study conducted in Japan, 22% [27]. Whereas, the result is in harmony with a study carried out in India, 27.9% [28] and far lower than studies done in Brazil, 55% [29], Gambia,58.6% [30], Uganda, 33% [31], Ghana, 48.9% [32], Nigeria, 52.5% [33], and Kenya, 51% [34]. Compared to previous studies in Ethiopia, the result is lower as compared to studies conducted in Gondar, 41.03% [22], and Jimma, 43.8% [23].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The nasopharyngeal carriage rate of 25.3% in the current study is higher than a study conducted in Japan, 22% [27]. Whereas, the result is in harmony with a study carried out in India, 27.9% [28] and far lower than studies done in Brazil, 55% [29], Gambia,58.6% [30], Uganda, 33% [31], Ghana, 48.9% [32], Nigeria, 52.5% [33], and Kenya, 51% [34]. Compared to previous studies in Ethiopia, the result is lower as compared to studies conducted in Gondar, 41.03% [22], and Jimma, 43.8% [23].…”
Section: Discussionsupporting
confidence: 69%
“…Age was found as a significantly associated factor for the nasopharyngeal carriage rate of Streptococcus pneumoniae. A similar study from Brazil documented children under 2 years of age group to be associated with pneumococcal colonization [29]. In addition, a study from India indicated the progressive decrease in the carriage rate with the increasing age of the children [28].…”
Section: Discussionmentioning
confidence: 99%
“…Pneumococcal carriage was inversely related to the number of rooms in the house but directly related to household size, thus suggesting that such factors might play an important role in sustaining the overall circulation of pneumococcal strains at the family-level. These findings were in accordance with Menezes et al [ 34 ], who recently described the same pathway among children in an urban community characterized by crowded environments in the households.…”
Section: Discussionsupporting
confidence: 93%
“…Studies assessing overall carriage rather than new acquisitions have reported lower carriage rates than those estimated from our cohort. A study of Brazilian children under 5 years old reported a 4-month risk of carriage of 74% prior to PCV introduction [ 27 ], equivalent to a yearly rate of 4.09 detections [ 28 ] and substantially lower than our estimated rates for both before and after PCV introduction. Similarly, studies from Bangladesh [ 29 ] and Thailand-Myanmar [ 11 ] of PCV-naïve populations report a 2-month colonization risk of approximately 50% in newborns, also equivalent to a yearly rate of slightly more than 4 detections.…”
Section: Discussioncontrasting
confidence: 60%